PROBLEMS OF ELECTROLYSIS AND ETCHING PRODUCTIONS WASTE PROCESSING - O. S. Komarov (Литьë и металлургия)
The methods of processing of the electrolysis and etching productions waste are examined and appraisal of possibility of their mastering in the Republic of Belarus is given.